ARCHITECHTURE FROM THE INDONESIAN PAST : Life and work of Fermont-Cuypers in the Indonesian archipelago 1927-1957 - Norbruis, Obbe, author 637596 (Volendam : LM Publishers, 2020)
In Architecture from the Indonesian Past, Obbe H. Norbruis tells the story of a celebrated Dutch architecture firm, its unique buildings, and their designers. Fermont-Cuypers designed many buildings significant in Indonesia's history beginning in 1927 when an uprising broke out against the Dutch in the colony. In the early 1930s, the firm drew up plans for many schools, churches, villas, and offices. At the end of the 1930s the firm began to design hospitals, head offices, hotels, and even a passenger terminal in Tanjung Priok. The expected tourism boom never materialized due to the German invasion of the Netherlands, and World War II soon had an impact on the region. After Indonesian independence, Fermont-Cuypers experienced a resurgence through 1958, designing many buildings that still exist today in cities such as Jakarta, Surabaya, Medan, Bandung, Makassar, and Palembang.